Individual motions of red blood cells in high-hematocrit blood flowing in a microchannel with complex geometries - Ishikawa, Takuji (2010)
Blood flow in a microchannel with complex geometries has been investigated to develop biomedical microdevices (e.g. Faivre et al., 2006) or to understand pathology in small vessels, such as lacunar infarcts. In a small channel, say 100 μm in diameter, the blood is no longer assumed to be a homogeneous fluid because the size of the red blood cells (RBCs) cannot be neglected compared to the generated flow field (the diameter of a RBC is about 8 μm). In such a case, we must treat the blood as a multiphase fluid, and investigate the motion of individual cells in discussing the flow field. In this study, we investigated the motion of RBCs in a microchannel with stenosis or bifurcation using a confocal micro-PTV system. We measured individual trajectories of RBCs under high Hct conditions (up to 20%), when the interactions between RBCs become significant. We discuss the effect of Hct on the flow field and cell-free layers, as well as the effect of deformability of RBCs on the cell-free layer thickness by hardening RBCs using a glutaraldehyde treatment.